INVARIANT SUBALGEBRAS OF THE SMALL N = 4 SUPERCONFORMAL ALGEBRA - Creutzig, Thomas; Linshaw, Andrew R.; Riedler, Wolfgang (Transformation Groups, 2021)
Various aspects of orbifolds and cosets of the small N = 4 superconformal algebra are studied First, we determine minimal strong generators for generic and specific levels As a corollary, we obtain the vertex algebra of global sections of the chiral de Rham complex on any complex Enriques surface We also identify orbifolds of cosets of the small N = 4 superconformal algebra with Com (Vl(sl2); Vl+1(sl2) W-5=2(sl4; frect)) and in addition at special levels with Grassmanian cosets and principal W-algebras of type A at degenerate admissible levels These coincidences lead us to a novel level-rank duality involving Grassmannian supercosets.
CRIS-Team Scopus Importer:2024-06-24